Case Report: Medullary Thyroid Cancer Workup Initiated by Unexpectedly High Procalcitonin Level—Endocrine Training Saves Life in the COVID-19 Unit - Sira, Livia; Balogh, Zoltán; Vitális, Eszter; Kovács, Dávid; Győry, Ferenc; Molnár, Csaba; Bodor, Miklos; Nagy, Endre V. (Frontiers in Endocrinology, 2021)
Background Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is a novel coronavirus that has caused a worldwide pandemic. The majority of medullary thyroid cancers present as a thyroid nodule. At the time of diagnosis, cervical lymph nodes and distant metastases are frequently detected. Case report Here we present a case of a 46 years old man with COVID pneumonia, who had persistently high serum procalcitonin levels in spite of normal C-reactive protein levels. The attending infectologist happened to be a colleague who spent some time, as part of her internal medicine rotation, in the Endocrine Ward and recalled that medullary thyroid cancer might be the cause. This led to the timely workup and treatment of the medullary cancer.